All-solid-state battery
By using a battery container structure with conductive paths and an elastic conductive member in an all-solid battery, the problem of unstable contact between the electrode and the conductive paths is solved, and the reliability of electrical connections and battery life is improved.
Patent Information
- Application Number
- CN202380051535.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-03
- Filing Date
- 2023-07-13
- Publication Date
- 2025-02-18
AI Technical Summary
In all-solid batteries, the prior art is difficult to improve the electrical connection reliability of the current collector and the electrode, resulting in unstable electrical connections and affecting the reliability and life of the battery.
The battery container structure adopts a concave container with a conductive path and a sealing body, and an elastic conductive member is built into the electrode laminated body to press the porous metal layer, so that the electrode contact between the electrode and the conductive path is achieved through the elastic force of the elastic conductive member.
It improves the electrical connection reliability in the current collecting structure, enhances the reliability and life of the battery, and reduces the deviation of internal resistance.
Smart Images

Figure CN119487663A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an all-solid-state battery having excellent electrical connectivity. Background Art
[0002] In recent years, with the development of portable electronic devices such as mobile phones and notebook personal computers, and the practical application of electric vehicles, there is a demand for small and lightweight batteries with high capacity and high energy density.
[0003] Currently, lithium cobalt oxide (LiCoO) is used as the positive electrode active material in lithium batteries, especially lithium ion batteries, which can meet this requirement. 2 ), lithium nickel oxide (LiNiO 2 ) or the like, graphite or the like is used as the negative electrode active material, and an organic electrolyte solution containing an organic solvent and a lithium salt is used as the non-aqueous electrolyte.
[0004] Furthermore, as the application equipment of lithium ion batteries further develops, lithium ion batteries are required to have a longer life, higher capacity, and higher energy density, and lithium ion batteries with longer life, higher capacity, and higher energy density are also required to have higher reliability.
[0005] However, the organic electrolyte used in lithium-ion batteries contains an organic solvent as a flammable substance, so when the battery is short-circuited or other abnormal conditions occur, the organic electrolyte may generate abnormal heat. In addition, with the high energy density of lithium-ion batteries in recent years and the increasing trend of the amount of organic solvent in the organic electrolyte, the reliability of lithium-ion batteries is further required.
[0006] Under the above situation, all-solid lithium batteries (all-solid batteries) that do not use organic solvents are also being studied. All-solid lithium batteries use a molded body of a solid electrolyte that does not use an organic solvent to replace the conventional organic solvent-based electrolyte, and there is no worry about abnormal heating of the solid electrolyte, and they have high reliability.
[0007] In addition, all-solid-state batteries are not only highly safe, but also highly reliable and environmentally resistant, and have a long lifespan. Therefore, they are expected to be maintenance-free batteries that can contribute to social development while also continuously contributing to peace of mind and safety. By providing all-solid-state batteries to society, we can contribute to the achievement of Goal 3 (Ensure healthy lives and promote well-being for all at all ages), Goal 7 (Ensure access to affordable, reliable, sustainable and modern energy for all), Goal 11 (Achieve inclusive, safe, resilient (risk-resistant) and sustainable cities and human settlements), and Goal 12 (Ensure sustainable production and consumption patterns) among the 17 goals of the Sustainable Development Goals (SDGs) set by the United Nations.
[0008] However, various outer packaging bodies are used in batteries such as all-solid-state batteries. For example, Patent Document 1 proposes a battery package comprising: an insulating substrate having a recess for accommodating a power-generating element and two external electrodes on the bottom surface; and a cover body that blocks the recess, has a conductive sheet that is considered to function as a current collector arranged on the upper surface of the power-generating element, and has wiring that electrically connects the conductive sheet to one of the two external electrodes.
[0009] In addition, Patent Document 1 describes that an elastic body (spacer) such as rubber is interposed between the cover and the conductive sheet, and the thickness of the spacer is thicker than the space between the cover and the conductive sheet, thereby using the elastic force of the spacer to press the conductive sheet against the upper surface of the electrode of the power generation element to achieve conductive connection. In addition, it is also described that a butyl rubber or the like that can be thermally expanded is used as a spacer, and after the outer body is sealed, the butyl rubber or the like is thermally expanded to produce the same effect as described above.
[0010] However, in the above-mentioned method using an elastic body such as rubber, when sealing the outer body, it is necessary to press the spacer with the cover body to reduce the thickness of the spacer while sealing, which easily leads to a decrease in sealing performance. In addition, in the method using butyl rubber capable of thermal expansion, the butyl rubber needs to be heated to a high temperature (about 200° C.) capable of thermal expansion, so it is not easy to adjust the heating conditions for thermal expansion of the butyl rubber in order to suppress the deterioration of the active material and the solid electrolyte and maintain the characteristics well.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: International Publication No. 2022 / 030424 Summary of the invention
[0014] Problems to be solved by the invention
[0015] In all-solid batteries, in addition to the case of using an outer casing in a form such as the battery package disclosed in Patent Document 1, there is a demand for the development of a technology for improving the reliability of conductive connection between a current collector and an electrode disposed in the outer casing.
[0016] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an all-solid-state battery having high electrical connection reliability in a current collecting structure.
[0017] Methods for solving problems
[0018] The all-solid-state battery of the present invention is characterized in that it comprises a battery container and an electrode stack accommodated in the battery container, the battery container comprises a concave container and a sealing body, the concave container has a bottom portion, a side wall portion and an opening portion, and has a conductive path from the inside to the outside, the opening portion of the concave container is covered by the sealing body, the electrode stack comprises a positive electrode, a negative electrode and a solid electrolyte layer between the positive electrode and the negative electrode, the positive electrode comprises a positive electrode mixture layer and a sheet-like porous metal substrate arranged on the surface of the positive electrode mixture layer, at least a portion of the porous metal substrate of the positive electrode, including an end portion on the positive electrode mixture layer side, is buried in the surface layer portion of the positive electrode mixture layer. The porous metal substrate of the positive electrode is integrated with the positive electrode mixture layer, and the other end of the porous metal substrate of the positive electrode is exposed on the surface of the positive electrode. The negative electrode comprises a negative electrode mixture layer and a sheet-shaped porous metal substrate arranged on the surface of the negative electrode mixture layer. At least a portion of the porous metal substrate of the negative electrode, including the end on the negative electrode mixture layer side, is buried in the surface layer of the negative electrode mixture layer and integrated with the negative electrode mixture layer. The other end of the porous metal substrate of the negative electrode is exposed on the surface of the negative electrode. An elastic conductive component is arranged between the electrode stack and the inner bottom surface of the sealing body, the elastic conductive component is connected to the conductive path, and presses the electrode stack toward the inner bottom surface of the concave container.
[0019] Effects of the Invention
[0020] According to the present invention, it is possible to provide an all-solid-state battery having high reliability of electrical connection in a current collecting structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a cross-sectional view schematically showing an example of the all-solid-state battery of the present invention.
[0022] Figure 2 This is a cross-sectional view schematically showing another example of the all-solid-state battery of the present invention.
[0023] Figure 3 It is schematically indicated Figure 2 A three-dimensional view of an elastic conductive component included in the all-solid-state battery shown.
[0024] Figure 4 This is a scanning electron microscope photograph of the surface of an example of an electrode of the all-solid-state battery of the present invention. DETAILED DESCRIPTION
[0025] Figure 1 2 is a longitudinal cross-sectional view schematically showing an example of the all-solid-state battery of the present invention. Figure 1The all-solid-state battery 100 shown includes an electrode stack 110 having a positive electrode 120 , a negative electrode 130 , and a solid electrolyte layer 140 interposed therebetween, and the electrode stack 110 is sealed in a battery container formed of a concave container 150 and a sealing body 160 .
[0026] The concave container 150 constituting the battery container is composed of a bottom surface portion 151 and a side wall portion 152 , and has an opening portion 153 opened on the upper side in the figure, and has a concave cross-section.
[0027] The positive electrode 120 includes a positive electrode mixture layer 121 and a porous metal substrate 122, wherein the entirety of the porous metal substrate 122 including the end portion on the positive electrode mixture layer 121 side is buried in the surface layer of the positive electrode mixture layer 121. That is, the entire portion where the porous metal substrate 122 exists corresponds to the region where the positive electrode mixture layer and the porous metal substrate coexist. Furthermore, in the positive electrode 120, the end portion ( Figure 1 It should be noted that the dotted line in the positive electrode 120 represents the boundary between the region in the positive electrode mixture layer 121 where the porous metal substrate does not coexist and the region where the positive electrode mixture layer and the porous metal substrate coexist, which is equivalent to the end of the porous metal substrate 122 on the positive electrode mixture layer 121 side.
[0028] The negative electrode 130 includes a negative electrode mixture layer 131 and a porous metal substrate 132, wherein the entire porous metal substrate 132 including the end portion on the negative electrode mixture layer 131 side is buried in the surface layer of the negative electrode mixture layer 131. That is, the entire area where the porous metal substrate 132 exists corresponds to the area where the negative electrode mixture layer and the porous metal substrate coexist. Furthermore, in the negative electrode 130, the end portion ( Figure 1 It should be noted that the dotted line in the negative electrode 130 represents the boundary between the region in the negative electrode mixture layer 131 where the porous metal substrate does not coexist and the region where the negative electrode mixture layer and the porous metal substrate coexist, which is equivalent to the end of the porous metal substrate 132 on the negative electrode mixture layer 131 side.
[0029] Connecting terminals 180 and 190 for electrically connecting to a device using the all-solid-state battery 100 are provided on the lower side of the concave container 150. The connecting terminal 180 is electrically connected to a conductive path 181 of the connecting terminal 180 extending from the inside of the concave container 150 to the outside. The conductive path 181 is electrically connected to the positive electrode 120 of the electrode stack 110 housed in the concave container 150, thereby conducting electricity between the positive electrode 120 of the electrode stack 110 and the connecting terminal 180. It should be noted that Figure 1In the all-solid-state battery 100, the porous metal layer 200 is located between the positive electrode 120 of the electrode stack 110 and the conductive path 181. Through the action of the porous metal layer 200, the conductivity between the positive electrode 120 and the conductive path 181 can be improved. In addition, the deviation of the internal resistance of each battery in the case of manufacturing multiple all-solid-state batteries can be suppressed (details will be described later).
[0030] In addition, the connection terminal portion 190 is electrically connected to a conductive path 191 of the connection terminal portion 190 extending from the inside to the outside of the concave container 150, and the conductive path 191 is arranged in the upper part of the electrode stack 110 in the figure, and is electrically connected to the negative electrode 130 via the elastic conductive member 170 in contact with the negative electrode 130 of the electrode stack 110. Thus, the negative electrode 130 of the electrode stack 110 and the connection terminal portion 190 are electrically connected.
[0031] The side wall portion 152 of the concave container 150 has a support portion 154 that supports the elastic conductive member 170. Figure 1 In the all-solid-state battery 100 shown, the support portion 154 is an extension portion formed at the upper end portion of the inner circumferential surface of the side wall portion 152 and extending radially, but the support portion for holding the conductive connecting component possessed by the all-solid-state battery may also be of other shapes as long as it can support the conductive connecting component.
[0032] The elastic conductive member 170 is formed of, for example, a metal thin plate, and a locking portion 171 corresponding to the support portion 154 of the concave container 150 is provided at its end. Figure 1 In the all-solid battery 100 shown, the locking portion 171 of the elastic conductive member 170 is a hook-shaped locking piece that is locked to the support portion 154. More specifically, the locking portion 171 extends from the edge of the elastic conductive member 170 toward the support portion 154 (toward the bottom of the figure) and has a front end that is folded back toward the lower surface of the support portion 154.
[0033] The ends of the conductive path 191 are exposed on the side and bottom surfaces of the support portion 154, and the conductive path 191 is in direct contact with the stopper portion 171 of the elastic conductive member 170, thereby electrically connecting the two. Thus, the elastic conductive member 170 functions as a current collector and becomes a part of the conductive path that electrically connects the negative electrode 130 and the connection terminal portion 190.
[0034] exist Figure 1In the all-solid battery 100 shown, when the elastic conductive member 170 is provided, first, after the electrode stack 110 is accommodated in the concave container 150, the elastic conductive member 170 is placed on the upper surface of the electrode stack 110. Then, in a state where the elastic conductive member 170 is placed on the upper surface of the electrode stack 110, the front end of the locking portion 171 is positioned between the upper surface of the electrode stack 110 and the lower surface of the support portion 154 in the axial direction of the electrode stack 110 (the up-down direction in the figure). Then, while the locking portion 171 of the elastic conductive member 170 is pressed toward the bottom surface portion 151 of the concave container 150, the front end of the locking portion 171 is locked to the lower surface of the support portion 154. At this time, the stopper 171 of the elastic conductive member 170 is pressed downward, so the elastic conductive member 170 (its recessed portion 172) is bent in the opposite direction to the electrode stack 110 while in contact with the electrode stack 110. As a result, the elastic conductive member 170 presses the electrode stack 110 toward the bottom portion 151 of the concave container 150 by its elastic force. That is, the elastic conductive member 170 functions as a plate spring. Through the above-mentioned action of the elastic conductive member 170, the electrical connection between the elastic conductive member 170 and the electrode stack 110 (its negative electrode 130), and the electrical connection between the electrode stack 110 (its positive electrode 120) and the conductive path 181 (the electrical connection between the electrode stack 110 and the porous metal layer 200, and the electrical connection between the porous metal layer 200 and the conductive path 181) become good, so that the reliability of the electrical connection between the components in the all-solid battery 100 is improved.
[0035] It should be noted that the elastic conductive member 170 has a recess 172 in contact with the upper surface of the electrode stack 110, and the bottom surface of the recess 172 is formed in a planar shape so that the electrode stack 110 can be pressed with a larger area. The elastic conductive member 170 has a function of pressing the electrode stack 110 toward the inner bottom surface of the concave container 150, but by making the elastic conductive member 170 have a shape with a planar recess 172, the elastic conductive member 170 and the electrode stack 110 (the negative electrode 130 thereof), and the electrode stack 110 (the positive electrode 120 thereof) and the conductive path 181 (the electrode stack 110 and the porous metal layer 200, and the porous metal layer 200 and the conductive path 181) can be pressed with a large area, respectively, and electrical connection between them can be performed with a larger area, so that the reliability of electrical connection between the components in the all-solid battery 100 is further improved.
[0036] in addition, Figure 2 2 is a longitudinal cross-sectional view schematically showing another example of the all-solid-state battery of the present invention. Figure 2 The all-solid battery 101 shown has an elastic conductive member 220. Figure 3The schematic representation is shown in Figure 2 The elastic conductive member 220 is a three-dimensional view of the all-solid-state battery 101 shown in FIG. The elastic conductive member 220 is composed of, for example, a metal thin plate, such as Figure 3 As shown, it is a quadrilateral in a plan view, but can be set to a shape corresponding to the plan view shape of the electrode stack and the concave container possessed by the all-solid-state battery.
[0037] Figure 2 The concave container 150 of the all-solid battery 101 shown has a plurality of support portions 155 for supporting the elastic conductive member 220 at the upper end of its side wall portion 152. The support portion 155 is formed as an extension extending in the circumferential direction of the inner peripheral surface of the side wall portion 152. More specifically, the support portion 155 is a plurality of recessed top walls formed on the inner peripheral surface of the side wall portion 152 toward the radial outer side. In addition, a portion of the conductive path 191 is exposed on the lower surface and side surface of the top wall. The number of support portions 155 is at least the number corresponding to the number of supported portions 221 of the elastic conductive member 220 described later.
[0038] The elastic conductive member 220 has a supported portion 221 and a planar portion 222. The supported portion 221 is provided in plurality in a position located radially outward of the electrode stack 110 of the all-solid-state battery 101 in a plan view corresponding to the position of the supporting portion 155. The supported portion 221 is a hook-shaped locking piece that is locked to the lower surface of the top wall of the supporting portion 155 and extends from the edge of the elastic conductive member 220 toward the supporting portion 155 (towards the support portion 155). Figure 2 In addition, the supported portion 221 has a front end that is folded back toward the lower surface of the support portion 155, i.e., the top wall. The front end of the supported portion 221 contacts the conductive path 191 exposed on the lower surface and side surface of the top wall of the support portion 155. Thus, the elastic conductive member 220 functions as a current collector and becomes a part of the conductive path that electrically connects the negative electrode 130 to the connection terminal portion 190.
[0039] The elastic conductive member 220 is supported by a support portion 155 formed on the inner circumference of the side wall portion 152 of the concave container 150, and covers a portion of the opening of the concave container 150. The area of the elastic conductive member 220 when viewed from above is smaller than the opening area of the concave container 150. It should be noted that even if the hook-shaped locking piece in the elastic conductive member 220 is not locked on the lower surface of the top wall of the support portion 155, as long as the elastic conductive member 220 can be fixed in a state where the hook-shaped locking piece is pressed into the recess formed on the inner circumference of the side wall portion 152, it is also considered that the elastic conductive member 220 is locked on the side wall portion 152 of the concave container 150.
[0040] like Figure 2As shown, the elastic conductive component 220 has a spring portion 223 that stands up from the planar portion 222 toward the negative electrode 130 of the electrode stack 110. The spring portion 223 contacts the upper surface of the negative electrode 130 (its porous metal substrate 132) of the electrode stack 110 in the figure, pressing the electrode stack 110 toward the inner bottom surface of the concave container 150.
[0041] In the elastic conductive member having a spring portion, the shape of the spring portion is not particularly limited as long as it can press the electrode stack toward the inner bottom surface of the concave container. Figure 2 and Figure 3 The spring portion 223 of the elastic conductive member 220 shown is a spring piece (hereinafter, the spring portion 223 may be referred to as the spring piece 223) that is inclined from the flat portion 222 toward the negative electrode 130 of the electrode stack 110. Figure 3 As shown, the spring piece 223 is formed by cutting a part of the plane portion 222 into a "U" shape, and is cantilever supported on the plane portion 222. That is, Figure 2 and Figure 3 The spring piece 223 in the elastic conductive member 220 shown is a leaf spring. If it is an elastic conductive member 220 of this form, it is sufficient to form the spring piece 223 on a part of the plane portion 222, so that the elastic conductive member and the all-solid battery can be manufactured more easily. In addition, by cutting the plane portion 222 to form the spring piece 223, the elastic conductive member and the all-solid battery can be manufactured more easily.
[0042] The spring piece 223 has a boundary 223a with the plane portion 222 and a tip 223b that is in contact with the negative electrode 130 of the electrode stack 110 and conducts electricity to the negative electrode 130. The spring piece 223 is bent at the boundary 223a and tilted toward the electrode stack 110 from the boundary 223a toward the tip 223b.
[0043] The height from the bottom surface of the plane portion 222 to the front end portion 223b (the height of the spring piece 223) of the elastic conductive member 220 before assembling the all-solid battery 101 is greater than the height from the bottom surface of the plane portion 222 to the front end portion 223b of the elastic conductive member 220 after assembling the all-solid battery 101. Thus, the electrode stack 110 can be pressed by the front end portion 223b of the spring piece 223, and good electrical connection between the elastic conductive member 220 and the negative electrode 130 of the electrode stack 110 can be maintained.
[0044] In addition, in the elastic conductive member 220, by forming the spring portion 223 from a spring sheet, the thickness of the elastic conductive member 220 other than the supported portion 221 can be reduced. For example, before assembling the all-solid battery 101, the thickness of the elastic conductive member 220 other than the supported portion 221 can be set to the sum of the thickness of the plate constituting the plane portion 222 and the height of the spring sheet 223. Specifically, the thickness of the plate 0.2 mm and the height of the spring sheet 0.5 mm can be added together to set the thickness of the elastic conductive member 220 other than the supported portion 221 to 0.7 mm.
[0045] In addition, regarding the spring piece 223, the length (the length from the boundary 223a to the front end 223b) can be set to 3mm, etc., and the width (the length in the direction perpendicular to the length direction) can be set to 1.5mm, etc. It should be noted that in the elastic conductive component having a spring piece, there can also be multiple spring pieces. In this case, for reasons such as preventing resonance, the shapes including the width and length of the spring piece can also be different. The thickness of the elastic conductive component 220 other than the supported portion 221 is preferably less than 1.2mm, more preferably less than 1mm, and particularly preferably less than 0.8mm. On the other hand, in order to enable the spring portion 223 to generate a good pressing force, the thickness of the elastic conductive component 220 other than the supported portion 221 is preferably greater than 0.3mm, more preferably greater than 0.4mm, and particularly preferably greater than 0.5mm.
[0046] Moreover, the edge of the elastic conductive member 220, that is, the position of the supported portion 221 can be freely set in the height direction (the thickness direction of the elastic conductive member 220), so even if a gap is formed between the sealing body 160 and the elastic conductive member 220, the distance between the sealing body 160 and the front end portion 223b of the spring piece 223 will not increase. As a result, the gap between the sealing body 160 and the electrode stack 110 can be suppressed from increasing, so that the capacity of the all-solid-state battery 101 can be increased. It should be noted that the thickness direction of the elastic conductive member 220 refers to Figure 2 The up-down direction (the height direction of the all-solid-state battery 101 ) can also be said to be a direction perpendicular to the bottom surface of the planar portion 222 .
[0047] The thickness of the entire elastic conductive member 220 including the supported portion 221 can be appropriately set according to the height from the bottom surface portion 151 in the side wall portion 152 of the concave container 150. In addition, the supported portion 221 only needs to have a height required to be locked to the supporting portion 155. The thickness of the entire elastic conductive member 220 including the supported portion 221 can be set to, for example, 3 mm or less, preferably 2.7 mm or less, and more preferably 2.5 mm or less.
[0048] In the elastic conductive member 220, the spring piece 223 may be formed by cutting the plane portion 222 as described above, or the spring piece 223 may be mounted on the bottom surface of the plane portion 222 by welding. In addition, a base for mounting the spring piece 223 may be pre-set separately from the plane portion 222, and the spring piece 223 may be mounted on the base so that the whole serves as a spring portion. That is, the spring piece 223 may be directly erected from the plane portion 222, or may be erected from the plane portion 223 by other elements such as the base. Furthermore, the spring piece 223 may be a shape in which both ends of the spring piece 223 are supported by the plane portion 222 to form a protrusion toward the electrode stack 110.
[0049] exist Figure 2 In the all-solid battery 101 shown in the figure, when the elastic conductive member 220 is provided, first, after the electrode stack 110 is accommodated in the concave container 150, it is placed on the upper surface of the electrode stack 110. When the elastic conductive member 220 is placed on the upper surface of the electrode stack 110, the front end of the supported portion 221 is in the axial direction ( Figure 2 The spring piece 223 of the elastic conductive member 220 is pressed downwardly, so that the spring piece 223 of the elastic conductive member 220 is pressed in the direction of the bottom surface 151 of the concave container 150 in the opposite direction to the negative electrode 130. At this time, the spring piece 223 presses the electrode stack 110 in the direction of the bottom surface 151 of the concave container 150 by its elastic force. As a result, the elastic conductive member 220 is in more stable contact with the electrode stack 110, and positional displacement will not occur due to vibration, etc., so that a good electrical connection can be maintained.
[0050] exist Figure 2 In the all-solid battery 101 shown, the concave container 150 has two support portions 155 , 155 , but the number of support portions 155 may be 3 or more. The supported portion 221 of the elastic conductive member 220 may be formed according to the number of support portions 155 .
[0051] It should be noted that as a method of fixing the edge (supported portion 221) of the elastic conductive member 220 to the inner circumferential surface of the side wall portion 152 of the concave container 150, a method of bonding the edge of the elastic conductive member 220 to the inner circumferential surface of the side wall portion 152 of the concave container 150 is also exemplified.
[0052] It should be noted that if Figure 1 and Figure 2 As shown, it is preferred that a gap is formed between the elastic conductive members 170 and 220 and the sealing body 160. That is, it is preferred that the elastic conductive members 170 and 220 do not contact the sealing body 160. Thus, even if the elastic conductive members 170 and 220 are pressed toward the sealing body 160 due to the volume change of the electrode stack 110 composed of the power generation element, the contact between the elastic conductive members 170 and 220 and the sealing body 160 can be avoided.
[0053] exist Figure 1 and Figure 2 In the all-solid-state battery shown, the electrode stack 110 is arranged in a manner such that the positive electrode 120 is located on the inner bottom surface side of the concave container 150 and the negative electrode 130 is located on the sealing body 160 side (elastic conductive component side), but the electrode stack can also be arranged in a manner such that the negative electrode is located on the inner bottom surface side of the concave container and the positive electrode is located on the sealing body side (elastic conductive component side) to form an all-solid-state battery.
[0054] In addition, the positive electrode of the all-solid-state battery has a positive electrode mixture layer and a sheet-like porous metal substrate disposed on the surface of the positive electrode mixture layer, at least a portion of the porous metal substrate of the positive electrode, including the end portion on the positive electrode mixture layer side, is buried in the surface portion of the positive electrode mixture layer and integrated with the positive electrode mixture layer, and the other end portion of the porous metal substrate of the positive electrode is exposed on the surface of the positive electrode. In addition, the negative electrode of the all-solid-state battery has a negative electrode mixture layer and a sheet-like porous metal substrate disposed on the surface of the negative electrode mixture layer, at least a portion of the porous metal substrate of the negative electrode, including the end portion on the negative electrode mixture layer side, is buried in the surface portion of the negative electrode mixture layer and integrated with the negative electrode mixture layer, and the other end portion of the porous metal substrate of the negative electrode is exposed on the surface of the negative electrode.
[0055] That is, in the electrode stack of the all-solid-state battery, in the positive electrode, the porous metal substrate that functions as a current collector is buried in the positive electrode mixture layer in a certain range in the thickness direction from the end (end face) on the positive electrode mixture layer side, and in the negative electrode, the porous metal substrate that functions as a current collector is buried in the negative electrode mixture layer in a certain range in the thickness direction from the end (end face) on the negative electrode mixture layer side. Therefore, in the positive electrode, the positive electrode mixture constituting the positive electrode mixture layer is retained in at least a portion of the pores of the porous metal substrate, so that the porous metal substrate and the positive electrode mixture layer are integrated, and in the negative electrode, the negative electrode mixture constituting the negative electrode mixture layer is retained in at least a portion of the pores of the porous metal substrate, so that the porous metal substrate and the negative electrode mixture layer are integrated, thereby, the electrical connection between the positive electrode mixture layer and the current collector (porous metal substrate), and the electrical connection between the negative electrode mixture layer and the current collector (porous metal substrate) become very good.
[0056] In addition, in the electrode stack of the all-solid-state battery, the end (end face) of the porous metal substrate of the positive electrode opposite to the positive electrode mixture layer side is exposed on the surface (the surface of the positive electrode), and the end (end face) of the porous metal substrate of the negative electrode opposite to the negative electrode mixture layer side is exposed on the surface (the surface of the negative electrode). Figure 1 and Figure 2 As shown, an all-solid-state battery is constructed using a battery container having a conductive path from the inside to the outside, and the porous metal substrate on the surface of the positive electrode and the porous metal substrate on the surface of the negative electrode are respectively in contact with the conductive path for the positive electrode (or the porous metal layer arranged adjacent to the positive electrode) and the conductive path for the negative electrode (or the porous metal layer arranged adjacent to the negative electrode), thereby achieving very good electrical connection between the positive electrode and the conductive path (or the porous metal layer arranged adjacent to the positive electrode) and very good electrical connection between the negative electrode and the conductive path (or the porous metal layer arranged adjacent to the negative electrode).
[0057] In the all-solid battery of the present invention, the electrical connection reliability in the current collection structure can be improved by the above-mentioned respective effects in the positive electrode and the negative electrode constituting the electrode stack and the above-mentioned effect brought about by the elastic conductive member.
[0058] The details of the all-solid-state battery are described below.
[0059] <Electrode Laminate>
[0060] The electrode stack has a positive electrode, a negative electrode, and a solid electrolyte layer interposed therebetween.
[0061] (positive electrode)
[0062] The positive electrode includes a positive electrode mixture layer containing a positive electrode active material and the like, and a sheet-shaped porous metal substrate functioning as a current collector.
[0063] When the all-solid-state battery is a primary battery, the positive electrode active material can be the same as the positive electrode active material used in the conventionally known non-aqueous electrolyte primary battery. Specifically, for example, manganese dioxide, lithium-containing manganese oxide (for example, LiMn 3 O 6 , a composite oxide having the same crystal structure as manganese dioxide (β-type, γ-type, or a structure in which β-type and γ-type are mixed) and having a Li content of 3.5% by mass or less, preferably 2% by mass or less, more preferably 1.5% by mass or less, and particularly preferably 1% by mass or less); Li a Ti 5 / 3 O 4 (4 / 3≤a<7 / 3) and other lithium-containing composite oxides; vanadium oxides; niobium oxides; titanium oxides; sulfides such as iron disulfide; graphite fluoride; Ag 2 S and other silver sulfides; NiO2 Nickel oxide, etc.
[0064] In addition, when the all-solid battery is used as the positive electrode of the secondary battery, the positive electrode active material can be the same as the positive electrode active material used in the conventionally known non-aqueous electrolyte secondary battery. Specifically, Li 1-x M r Mn 2-r O 4 (wherein M is at least one element selected from the group consisting of Li, Na, K, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Zr, Fe, Co, Ni, Cu, Zn, Al, Sn, Sb, In, Nb, Ta, Mo, W, Y, Ru and Rh, 0≤x≤1, 0≤r≤1) spinel lithium manganese composite oxide, Li r Mn (1-s-t) Ni s M t O (2-u) F v (wherein M is at least one element selected from the group consisting of Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr and W, 0≤r≤1.2, 0<s<0.5, 0≤t≤0.5, u+v<1, -0.1≤u≤0.2, 0≤v≤0.1) a layered compound represented by 1-x Co 1-r M r O 2 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, V, Cr, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤1, 0≤r≤0.5) represented by a lithium cobalt composite oxide, Li 1-x Ni 1-r M r O 2 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤1, 0≤r≤0.5) lithium nickel composite oxide, Li 1+s-x M 1-r N r PO 4 F s(wherein M is at least one element selected from the group consisting of Fe, Mn and Co, N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V and Ba, 0≤x≤1, 0≤r≤0.5, 0≤s≤1) represented by an olivine-type composite oxide, Li 2-x M 1-r N r P 2 O 7 (wherein M is at least one element selected from the group consisting of Fe, Mn and Co, N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V and Ba, 0≤x≤2, 0≤r≤0.5) pyrophosphate compounds represented by, etc., may be used alone or in combination of two or more.
[0065] In the case where the all-solid battery is a secondary battery, the average particle size of the positive electrode active material is preferably 1 μm or more, more preferably 2 μm or more, and preferably 10 μm or less, more preferably 8 μm or less. In addition, the positive electrode active material can be a primary particle or a secondary particle formed by agglomeration of primary particles. If a positive electrode active material having an average particle size in the above range is used, the interface with the solid electrolyte contained in the positive electrode increases, so the output characteristics of the battery are further improved.
[0066] The average particle size of various particles (positive electrode active material, solid electrolyte, etc.) referred to in this specification refers to the value of 50% diameter (D) in the cumulative fraction based on volume when the integrated volume is obtained from particles with a small particle size using a particle size distribution measuring device (Microtrac particle size distribution measuring device "HRA9320" manufactured by Nikkiso Co., Ltd., etc.). 50 ).
[0067] When the all-solid-state battery is a secondary battery, the positive electrode active material preferably has a reaction inhibition layer on its surface for inhibiting the reaction with the solid electrolyte contained in the positive electrode.
[0068] In the positive electrode mixture layer, if the positive electrode active material is in direct contact with the solid electrolyte, the solid electrolyte is oxidized to form a resistance layer, and the ion conductivity in the positive electrode mixture layer may be reduced. By providing a reaction inhibition layer on the surface of the positive electrode active material to inhibit the reaction with the solid electrolyte, the direct contact between the positive electrode active material and the solid electrolyte is prevented, thereby suppressing the reduction of ion conductivity in the positive electrode mixture layer caused by oxidation of the solid electrolyte.
[0069] The reaction inhibition layer can be made of a material having ion conductivity and capable of inhibiting the reaction between the positive electrode active material and the solid electrolyte. Examples of materials capable of constituting the reaction inhibition layer include oxides containing Li and at least one element selected from the group consisting of Nb, P, B, Si, Ge, Ti, and Zr. More specifically, LiNbO 3 Containing Nb oxide, Li 3 PO 4 , Li 3 BO 3 , Li 4 SiO 4 , Li 4 GeO 4 、LiTiO 3 、LiZrO 3 , Li 2 WO 4 The reaction inhibition layer may contain only one of these oxides, or two or more of these oxides, and multiple of these oxides may form a composite compound. Among these oxides, Nb-containing oxides are preferably used, and LiNbO is more preferably used. 3 .
[0070] The reaction suppression layer is preferably present on the surface in an amount of 0.1 to 1.0 parts by mass relative to 100 parts by mass of the positive electrode active material. Within this range, the reaction between the positive electrode active material and the solid electrolyte can be suppressed well.
[0071] Examples of a method for forming a reaction suppression layer on the surface of a positive electrode active material include a sol-gel method, a mechanofusion method, a CVD method, a PVD method, and an ALD method.
[0072] From the viewpoint of further increasing the energy density of the all-solid-state battery, the content of the positive electrode active material in the positive electrode mixture is preferably 60 to 85% by mass.
[0073] The positive electrode mixture may contain a conductive additive. Specific examples thereof include carbon materials such as graphite (natural graphite, artificial graphite), graphene, carbon black, carbon nanofibers, and carbon nanotubes. It should be noted that, for example, when Ag is used as the active material, 2 In the case of S, Ag with conductivity is generated during the discharge reaction, so the conductive auxiliary agent may not be contained. When the positive electrode mixture contains a conductive auxiliary agent, when the content of the positive electrode active material is set to 100 parts by mass, the content of the conductive auxiliary agent is preferably 1.0 parts by mass or more, preferably 7.0 parts by mass or less, and more preferably 6.5 parts by mass or less.
[0074] In addition, the positive electrode mixture may contain a binder. As a specific example, fluororesins such as polyvinylidene fluoride (PVDF) can be cited. It should be noted that, for example, as in the case where a sulfide-based solid electrolyte is contained in the positive electrode mixture (details are described later), in the case where good formability can be ensured when forming the positive electrode mixture layer even without using a binder, the positive electrode mixture may not contain a binder.
[0075] In the positive electrode mixture, when a binder is required, its content is preferably 15% by mass or less, and preferably 0.5% by mass or more. On the other hand, in the positive electrode mixture, when formability can be obtained even without a binder, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and further preferably 0% by mass (i.e., without a binder).
[0076] The positive electrode mixture preferably contains a solid electrolyte.
[0077] The solid electrolyte contained in the positive electrode mixture is not particularly limited as long as it has lithium ion conductivity, and for example, a sulfide-based solid electrolyte, a hydride-based solid electrolyte, a halide-based solid electrolyte, an oxide-based solid electrolyte, etc. can be used.
[0078] Examples of sulfide-based solid electrolytes include Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 SP 2 S 5 -GeS 2 , Li 2 SB 2 S 3 In addition, thio-LISICON type solid electrolytes [Li 10 G 2 S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Wait 12-12a-b+c+6d- e M 1 3+a-b-c-d M 2 b M 3 c M 4 d M 5 12-e Xe (wherein, M 1 is Si, Ge or Sn, M 2 is P or V, M 3 is Al, Ga, Y or Sb, M 4 is Zn, Ca or Ba, M 5 is S, or S and O, X is F, Cl, Br or I, 0 ≤ a < 3, 0 ≤ b + c + d ≤ 3, 0 ≤ e ≤ 3)), a solid electrolyte having a thiogermanate-type crystal structure.
[0079] As the hydride-based solid electrolyte, for example, LiBH 4 , LiBH 4 and a solid solution with the following alkali metal compound (for example, a solid solution of LiBH 4 and the alkali metal compound in a molar ratio of 1:1 to 20:1), etc. As the alkali metal compound in the above solid solution, at least one selected from the group consisting of lithium halides (LiI, LiBr, LiF, LiCl, etc.), rubidium halides (RbI, RbBr, RbF, RbCl, etc.), cesium halides (CsI, CsBr, CsF, CsCl, etc.), lithium amide, rubidium amide, and cesium amide can be cited.
[0080] As the halide-based solid electrolyte, for example, monoclinic LiAlCl 4 , defective spinel-type or layered-structured LiInBr 4 , monoclinic Li 6-3m Y m X 6 (wherein, 0 < m < 2 and X = Cl or Br), etc. In addition, for example, known substances described in International Publication No. 2020 / 070958 and International Publication No. 2020 / 070955 can be used.
[0081] As the oxide-based solid electrolyte, for example, garnet-type Li 7 La 3 Zr 2 O 12 , NASICON-type Li 1+O Al 1+ O Ti 2-O (PO 4 ) 3 , Li 1+p Al 1+p Ge 2-p (PO 4 ) 3 , perovskite-type Li 3q La 2 / 3-q TiO 3 , etc.
[0082] Among these solid electrolytes, from the perspective of high lithium ion conductivity, a sulfide-based solid electrolyte is preferred, and a sulfide-based solid electrolyte containing Li and P is more preferred. From the perspective of higher lithium ion conductivity and high chemical stability, a sulfide-based solid electrolyte having an argyrodite-type crystal structure is further preferred.
[0083] As a sulfide-based solid electrolyte having an argyrodite-type crystal structure, for example, Li 6 PS 5 Cl, etc., are substances represented by the following general composition formula (1) or the following general composition formula (2).
[0084] Li 7-x+y PS 6-x Cl x+y (1)
[0085] In the above general composition formula (1), 0.05≤y≤0.9, -3.0x+1.8≤y≤-3.0x+5.7.
[0086] Li 7-a PS 6-a Cl b Br c (2)
[0087] In the above general composition formula (2), a=b+c, 0<a≤1.8, 0.1≤b / c≤10.0.
[0088] From the viewpoint of reducing grain boundary resistance, the average particle size of the solid electrolyte is preferably greater than 0.1 μm, more preferably greater than 0.2 μm. On the other hand, from the viewpoint of forming a sufficient contact interface between the active material and the solid electrolyte, it is preferably less than 10 μm, more preferably less than 5 μm.
[0089] From the viewpoint of further improving the ionic conductivity in the positive electrode and further improving the output characteristics of the all-solid battery, when the content of the positive electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the positive electrode mixture is preferably 10 parts by mass or more, more preferably 15 parts by mass or more. However, if the amount of the solid electrolyte in the positive electrode mixture is too much, the amount of other components decreases, and the effect brought by them is likely to decrease. Therefore, when the content of the positive electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the positive electrode mixture is preferably 65 parts by mass or less, more preferably 60 parts by mass or less.
[0090] The sheet-like porous metal substrate in the positive electrode preferably uses a foamed metal porous body. As a specific example of the foamed metal porous body, "Celmet (registered trademark)" of Sumitomo Electric Industries, Ltd. can be cited. It should be noted that the thickness of such a porous metal substrate before being used for the positive electrode (electrode stack) is usually greater than the above-mentioned thickness (thickness in the positive electrode) (for example, the thickness before being compressed is preferably 0.1 mm or more, more preferably 0.3 mm or more, particularly preferably 0.5 mm or more, on the other hand, preferably 3 mm or less, more preferably 2 mm or less, particularly preferably 1.5 mm or less), when the electrode stack described later is manufactured, it is compressed in the thickness direction, and its thickness becomes a value described later.
[0091] In order to easily fill the positive electrode mixture into the pores of the porous metal substrate and easily integrate the porous metal substrate and the positive electrode mixture layer in the process of pressurizing the porous metal substrate and the positive electrode mixture, the porosity of the porous metal substrate before being compressed is preferably 80% or more, more preferably 90% or more, and particularly preferably 95% or more. On the other hand, in order to increase the conductivity by making the amount of the substrate above a certain level, the porosity is preferably 99.5% or less, more preferably 99% or less, and particularly preferably 98.5% or less.
[0092] In the positive electrode, from the viewpoint of more reliably integrating the porous metal substrate and the positive electrode mixture layer, the thickness of the portion of the porous metal substrate buried in the positive electrode mixture layer is preferably greater than 10% of the thickness of the porous metal substrate (the thickness of the entire porous metal substrate, including the thickness of the portion where the positive electrode mixture layer coexists. Unless otherwise specified, the thickness of the porous metal substrate shall apply the same below), and more preferably greater than 20%.
[0093] In addition, in the positive electrode, in order to reduce the resistance when contacting with the conductive path in the battery container (or the porous metal layer adjacent to the positive electrode), the end of the porous metal substrate on the opposite side of the positive electrode mixture layer is preferably not buried in the positive electrode mixture layer, and the end of the positive electrode (the surface of the positive electrode) is only composed of the porous metal substrate. That is, when the porous metal substrate is compressed in the thickness direction during the manufacture of the electrode stack described later, the pores at the end of the porous metal substrate are preferably crushed and disappear, and only the porous metal substrate is exposed on the surface of the positive electrode. However, a part of the pores at the end of the porous metal substrate may not be crushed, but may be filled with a positive electrode mixture therein, and a part of the positive electrode mixture may be exposed on the surface of the positive electrode together with the end of the porous metal substrate within a range that does not have a large impact on the contact resistance with the conductive path (or the porous metal layer adjacent to the positive electrode).
[0094] Figure 4A scanning electron microscope (SEM) photograph of the surface of an example of a positive electrode is shown in FIG. Figure 4 In the illustrated positive electrode, the end of the porous metal substrate 122 is exposed on the surface, but part of the positive electrode mixture 121 a also enters the pores existing at the end of the porous metal substrate and is exposed on the surface of the positive electrode.
[0095] However, the greater the proportion (area ratio) of the positive electrode mixture exposed on the surface of the positive electrode, the greater the contact resistance between the porous metal substrate and the conductive path of the battery container (or the porous metal layer arranged adjacent to the positive electrode). Therefore, the proportion of the area of the exposed positive electrode mixture in the positive electrode surface is preferably less than 50% when viewed from above, more preferably less than 25%, further preferably less than 15%, and particularly preferably less than 10%.
[0096] In the positive electrode, when at least a portion of the porous metal substrate is buried in the positive electrode mixture layer, from the viewpoint of more reliably integrating the porous metal substrate and the positive electrode mixture layer, the thickness of the porous metal substrate is preferably 1% or more of the thickness of the entire positive electrode mixture layer (including the thickness of the portion coexisting with the porous metal substrate. Unless otherwise specified, the "thickness of the positive electrode mixture layer" referred to below refers to the "thickness of the entire positive electrode mixture layer" referred to herein), more preferably 2% or more, and particularly preferably 3% or more. In addition, from the viewpoint of improving the filling property of the positive electrode mixture layer in the positive electrode, the thickness of the porous metal substrate is preferably less than 30% of the thickness of the positive electrode mixture layer, more preferably less than 20%, and particularly preferably less than 10%.
[0097] It should be noted that in the positive electrode, the thickness of the porous metal substrate is preferably 10 μm or more, more preferably 20 μm or more, particularly preferably 30 μm or more, on the other hand, preferably 300 μm or less, more preferably 200 μm or less, particularly preferably 100 μm or less. In addition, the thickness of the positive electrode mixture layer is preferably 0.2 mm or more, more preferably 0.5 mm or more, particularly preferably 0.7 mm or more, on the other hand, preferably 2 mm or less, more preferably 1.7 mm or less, particularly preferably 1.5 mm or less.
[0098] The thickness of the porous metal substrate, the thickness of the positive electrode mixture layer, and the thickness of the negative electrode mixture layer described later in this specification are respectively obtained by observing the cross section of the thickness direction of the positive electrode or the negative electrode using SEM at a magnification of 50 to 1000 times to find the maximum value of the width in the thickness direction of the area where the porous metal substrate can be confirmed and the area where the positive electrode mixture or the negative electrode mixture can be confirmed. In addition, the thickness of the portion of the porous metal substrate buried in the positive electrode mixture layer or the negative electrode mixture layer is obtained by finding the maximum value of the width in the thickness direction of the portion where the area where the porous metal substrate can be confirmed overlaps with the area where the positive electrode mixture can be confirmed or the area where the negative electrode mixture can be confirmed (the values in the embodiments described later are obtained by these methods).
[0099] In addition, the proportion of the positive electrode mixture exposed on the surface of the positive electrode (area ratio) and the proportion of the negative electrode mixture exposed on the surface of the negative electrode (area ratio) are calculated by taking the ratio (A / B) of the sum A of the areas of the exposed portions of the positive electrode mixture or the negative electrode mixture in an image of the surface of the positive electrode or the negative electrode observed using SEM at a magnification of 50 to 200 times to the area B of the entire positive electrode or the negative electrode (the values in the examples described later are calculated using this method).
[0100] (negative electrode)
[0101] The negative electrode includes a negative electrode mixture layer containing a negative electrode active material and the like, and a sheet-like porous metal substrate functioning as a current collector.
[0102] As the negative electrode active material, for example, carbon materials such as graphite, lithium titanium oxide (lithium titanate, etc.), simple substances containing elements such as Si and Sn, compounds (oxides, etc.) and alloys thereof, etc. In addition, lithium metal and lithium alloys (lithium-aluminum alloys, lithium-indium alloys, etc.) can also be used as negative electrode active materials.
[0103] From the viewpoint of further increasing the energy density of the battery, the content of the negative electrode active material in the negative electrode mixture is preferably 40 to 80% by mass.
[0104] The negative electrode mixture may contain a conductive aid. As a specific example, the same conductive aid as the material that can be contained in the positive electrode mixture can be cited. When the content of the negative electrode active material is set to 100 parts by mass, the content of the conductive aid in the negative electrode mixture is preferably 10 to 30 parts by mass.
[0105] In addition, the negative electrode mixture may contain a binder. As a specific example, the same substance as the binder previously exemplified as a substance that can be contained in the positive electrode mixture can be cited. It should be noted that, for example, as in the case where the negative electrode mixture contains a sulfide-based solid electrolyte (described later), the negative electrode mixture may not contain a binder if good formability can be ensured when forming the negative electrode mixture layer even without using a binder.
[0106] In the negative electrode mixture, when a binder is required, its content is preferably 15% by mass or less, and preferably 0.5% by mass or more. On the other hand, in the negative electrode mixture, when formability can be obtained even without a binder, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and further preferably 0% by mass (i.e., no binder).
[0107] The negative electrode mixture preferably contains a solid electrolyte. As a specific example, the same substance as the solid electrolyte previously exemplified as a substance that can be contained in the positive electrode mixture can be cited. Among the solid electrolytes exemplified above, it is preferred to use a sulfide-based solid electrolyte from the perspective of having high lithium ion conductivity and having the function of improving the formability of the negative electrode mixture, and it is more preferred to use a sulfide-based solid electrolyte having a argyrodite-type crystal structure, and it is further preferred to use a solid electrolyte represented by the above-mentioned composition formula (1) or the above-mentioned composition formula (2).
[0108] For the same reasons as in the case of the positive electrode mixture, the average particle size of the solid electrolyte in the negative electrode mixture is preferably 0.1 μm or more, more preferably 0.2 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less.
[0109] From the viewpoint of further improving the ion conductivity in the negative electrode and further improving the output characteristics of the all-solid battery, when the content of the negative electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the negative electrode mixture is preferably 30 parts by mass or more, more preferably 35 parts by mass or more. However, if the amount of the solid electrolyte in the negative electrode mixture is too much, the amount of other components decreases, and the effect brought by them is likely to decrease. Therefore, when the content of the negative electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the negative electrode mixture is preferably 130 parts by mass or less, more preferably 110 parts by mass or less.
[0110] The sheet-like porous metal substrate in the negative electrode is preferably a foamed metal porous body in the same manner as the positive electrode. As a specific example of the foamed metal porous body, "Celmet (registered trademark)" of Sumitomo Electric Industries, Ltd. can be cited. It should be noted that the thickness of such a porous metal substrate before being used for the negative electrode (electrode stack) is usually greater than the above-mentioned thickness (thickness in the negative electrode) (for example, the thickness before being compressed is preferably 0.1 mm or more, more preferably 0.3 mm or more, particularly preferably 0.5 mm or more, on the other hand, preferably 3 mm or less, more preferably 2 mm or less, particularly preferably 1.5 mm or less), when the electrode stack described later is manufactured, the porous metal substrate is compressed in the thickness direction, and its thickness becomes a value described later.
[0111] In order to easily fill the pores of the porous metal substrate with the negative electrode mixture and easily integrate the porous metal substrate and the negative electrode mixture layer in the process of pressurizing the porous metal substrate and the negative electrode mixture, the porosity of the porous metal substrate before being compressed is preferably 80% or more, more preferably 90% or more, and particularly preferably 95% or more. On the other hand, in order to increase the conductivity by making the amount of the substrate above a certain level, the porosity is preferably 99.5% or less, more preferably 99% or less, and particularly preferably 98.5% or less.
[0112] In the negative electrode, from the viewpoint of more reliably integrating the porous metal substrate and the negative electrode mixture layer, the thickness of the portion of the porous metal substrate buried in the negative electrode mixture layer is preferably 10% or more of the thickness of the porous metal substrate (the thickness of the entire porous metal substrate, including the thickness of the portion where the negative electrode mixture layer coexists. Unless otherwise specified, the thickness of the porous metal substrate shall apply the same below), and more preferably 20% or more.
[0113] In addition, in the negative electrode, in order to reduce the resistance when contacting with the conductive path in the battery container (or the porous metal layer adjacent to the negative electrode), it is preferred that the end of the porous metal substrate on the opposite side of the negative electrode mixture layer is not buried in the negative electrode mixture layer, and the end of the negative electrode (the surface of the negative electrode) is only composed of the porous metal substrate. That is, when the porous metal substrate is compressed in the thickness direction during the manufacture of the electrode stack described later, the pores at the end of the porous metal substrate are preferably crushed and disappear, and only the porous metal substrate is exposed on the surface of the negative electrode. However, a part of the pores at the end of the porous metal substrate may not be crushed, but may be filled with a negative electrode mixture, and a part of the negative electrode mixture may be exposed on the surface of the negative electrode together with the end of the porous metal substrate within a range that does not have a large impact on the contact resistance with the conductive path (or the porous metal layer adjacent to the negative electrode).
[0114] However, the greater the proportion of the negative electrode mixture exposed on the surface of the negative electrode (area ratio), the greater the contact resistance between the porous metal substrate and the conductive path of the battery container (or the porous metal layer arranged adjacent to the negative electrode). Therefore, the proportion of the area of the exposed negative electrode mixture in the negative electrode surface is preferably less than 50% when viewed from above, more preferably less than 25%, further preferably less than 15%, and particularly preferably less than 10%.
[0115] In the negative electrode, when at least a portion of the porous metal substrate is buried in the negative electrode mixture layer, from the viewpoint of more reliably integrating the porous metal substrate and the negative electrode mixture layer, the thickness of the porous metal substrate is preferably 1% or more of the thickness of the entire negative electrode mixture layer (including the thickness of the portion coexisting with the porous metal substrate. Unless otherwise specified, the "thickness of the negative electrode mixture layer" referred to below refers to the "thickness of the entire negative electrode mixture layer" referred to herein), more preferably 2% or more, and particularly preferably 3% or more. In addition, from the viewpoint of improving the packing property of the negative electrode mixture layer in the negative electrode, the thickness of the porous metal substrate is preferably less than 30% of the thickness of the negative electrode mixture layer, more preferably less than 20%, and particularly preferably less than 10%.
[0116] It should be noted that in the negative electrode, the thickness of the porous metal substrate is preferably 10 μm or more, more preferably 20 μm or more, particularly preferably 30 μm or more, on the other hand, preferably 300 μm or less, more preferably 200 μm or less, particularly preferably 100 μm or less. In addition, the thickness of the negative electrode mixture layer is preferably 0.2 mm or more, more preferably 0.5 mm or more, particularly preferably 0.7 mm or more, on the other hand, preferably 2 mm or less, more preferably 1.7 mm or less, particularly preferably 1.5 mm or less.
[0117] (Solid electrolyte layer)
[0118] In the electrode stack, the solid electrolyte layer is interposed between the positive electrode and the negative electrode. As a specific example of a solid electrolyte constituting the solid electrolyte layer, the same substance as the solid electrolyte previously exemplified as a substance that can be contained in the positive electrode mixture can be cited. Among the solid electrolytes exemplified above, from the perspective of high lithium ion conductivity and the function of improving formability, it is preferred to use a sulfide-based solid electrolyte, more preferably a sulfide-based solid electrolyte having a argyrodite-type crystal structure, and further preferably a solid electrolyte represented by the above-mentioned composition formula (1) or the above-mentioned composition formula (2).
[0119] The solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.
[0120] The thickness of the solid electrolyte layer is preferably 10 to 200 μm.
[0121] (Method for producing electrode stack)
[0122] The electrode stack can be produced, for example, by a production method including the following first to third steps.
[0123] In the first step, the electrode mixture (positive electrode mixture or negative electrode mixture) is put into a mold and pressure-molded. The surface pressure of the pressure-molding in the first step is preferably 30 MPa to 500 MPa, for example.
[0124] In the following second step, a porous metal substrate is placed on the electrode mixture formed by pressure in the first step, and in the following third step, the electrode mixture and the porous metal substrate are pressurized. By pressurizing in the third step, the porous metal substrate is embedded in the electrode mixture from the end of the electrode mixture side, and the electrode mixture is further compressed, and the porous metal substrate is compressed in the thickness direction, so that the electrode mixture layer (positive electrode mixture layer or negative electrode mixture layer) is integrated with the porous metal substrate to form an electrode (positive electrode or negative electrode).
[0125] As described above, in the third step, the porous metal substrate is compressed in the thickness direction, and as the degree of compression, from the viewpoint of making the porous metal substrate and the electrode mixture layer more reliable, it is preferred that the thickness of the porous metal substrate after compression is less than 30% of the thickness before compression, more preferably less than 20%, and particularly preferably less than 10%. In addition, from the viewpoint of maintaining a certain amount of electrode mixture in the voids of the porous metal substrate, thereby improving the bonding strength between the porous metal substrate and the electrode mixture layer, it is preferred that the thickness of the porous metal substrate after compression in the third step is set to more than 1% of the thickness before compression, and more preferably more than 2%.
[0126] In order to compress and mold the electrode mixture and fully improve the density of the electrode mixture layer, the surface pressure during the pressurization in the third step is preferably 800MPa or more, more preferably 1000MPa or more, and particularly preferably 1200MPa or more. The upper limit of the surface pressure during the pressurization in the third step is not particularly specified, but in general pressurizing devices, usually about 2000MPa is the upper limit.
[0127] By going through the above-mentioned first step to the above-mentioned third step, an electrode (positive electrode or negative electrode) having the following structure can be obtained: at least a portion of the porous metal substrate including the end portion on the electrode mixture layer side (a certain range in the thickness direction from the end portion of the porous metal substrate) is buried in the surface portion of the electrode mixture layer and integrated with the electrode mixture layer, and the other end portion of the porous metal substrate is exposed on the surface of the electrode.
[0128] It should be noted that if the surface pressure during pressurization in the third step becomes high, cracks may occur when the porous metal substrate is compressed. However, even if it is cut and fragmented, as long as its end is exposed on the surface of the electrode, it can help reduce the contact resistance.
[0129] The positive electrode and the negative electrode can be produced through the above-mentioned first step, second step, and third step, and these can be arranged on both sides of the solid electrolyte layer and pressed as necessary to form an electrode stack.
[0130] Furthermore, before the first step, a preparatory step is provided for placing a solid electrolyte into a mold for pressure molding. In this preparatory step, an electrode mixture (positive electrode mixture or negative electrode mixture) is placed on the pressure-molded solid electrolyte. Then, the first step, the second step and the third step are sequentially performed to produce an integrated product of a solid electrolyte layer and an electrode (positive electrode or negative electrode), which can also be used for an electrode stack.
[0131] The surface pressure during the press molding in the preliminary step is preferably, for example, 30 MPa to 120 MPa.
[0132] Alternatively, an electrode stack may be manufactured by forming one of the positive and negative electrodes on a single surface of a solid electrolyte layer through a preparatory step, a first step, a second step, and a third step, and further sequentially performing the first step, a second step, and a third step on the other surface of the solid electrolyte layer to form the other electrode (negative electrode or positive electrode).
[0133] <Battery Container>
[0134] The battery container (outer body) of the all-solid-state battery may be a structure having a concave container and a sealing body, wherein the concave container has a conductive path extending from the inside of the concave container to the outside, and the porous metal substrate on the surface of the electrode (positive electrode and negative electrode) of the electrode stack is in contact with the conductive path so that the electrode and the conductive path can be electrically connected. For example, Figure 1 and Figure 2 The battery container of the form shown. In such a battery container, the concave container can be a container made of ceramics or resin. In addition, the sealing body can be a sealing body made of ceramics, resin, or metal (iron-nickel alloy, iron-nickel-cobalt alloy, etc., such as iron-based alloy).
[0135] In the concave container, the connection terminal portion and the conductive path connecting the electrode of the electrode stack to the connection terminal portion can be composed of metals such as manganese, cobalt, nickel, copper, molybdenum, silver, palladium, tungsten, platinum, gold, etc., or alloys containing these metals.
[0136] The concave container and the sealing body can be sealed by bonding with an adhesive. In addition, when a metal sealing body is used, Figure 1 and Figure 2 As shown, a sealing ring 210 made of metal (iron-nickel alloy, iron-nickel-cobalt alloy, or other iron-based alloy) may be pre-arranged on the sealing body 160 side (upper side in the figure) of the side wall portion 152 of the concave container 150, so that the sealing body side of the side wall portion formed of metal can be sealed by welding the concave container and the sealing body.
[0137] The shape of the battery container of the all-solid-state battery in plan view may be circular or may be a polygon such as a quadrilateral (square, rectangle).
[0138] <Elastic Conductive Member>
[0139] The elastic conductive member is not particularly limited as long as it functions as a leaf spring that presses the electrode stack toward the inner bottom surface of the concave container. Figure 1 The elastic conductive member shown in the figure has a cross-sectional shape having a locking portion 171 having a shape corresponding to the support portion 154 of the concave container 150 and a concave portion 172 for pressing the electrode stack 110; Figure 2 and Figure 3 The elastic conductive member shown in the figure has a supported portion 221 having a shape corresponding to the supporting portion 155 of the concave container 150 and a flat portion 222 having a spring portion (spring piece) 223 .
[0140] The elastic conductive member can be formed by a plate made of nickel, iron, copper, chromium, cobalt, titanium, aluminum, or an alloy thereof. In the above examples, the metal constituting the elastic conductive member is preferably a stainless steel plate, a metal obtained by nickel-plating a stainless steel plate, or the like, and more preferably a spring stainless steel such as SUS301-CSP, SUS304-CSP, SUS316-CSP, SUS420J2-CSP, SUS631-CSP, or SUS632J1-CSP in order to facilitate the function as a leaf spring.
[0141] In order to make the pressing force on the electrode stack above a certain level, the thickness of the metal plate constituting the elastic conductive member is preferably 0.05 mm or more, more preferably 0.07 mm or more, and particularly preferably 0.1 mm or more. On the other hand, in order to prevent the elastic conductive member from becoming too thick and increasing the storage volume in the battery container, and to easily deform the elastic conductive member so that it can be easily stuck to the side wall of the concave container, the thickness of the metal plate constituting the elastic conductive member is preferably 0.5 mm or less, more preferably 0.4 mm or less, and particularly preferably 0.3 mm or less.
[0142] In addition, if Figure 1As shown, when the elastic conductive member has a concave portion for pressing the electrode stack, the area of the portion of the concave portion in contact with the electrode stack is preferably 3 to 45 mm from the viewpoint that the elastic conductive member can press the electrode stack more uniformly at the contact surface with the electrode stack. 2 The depth of the recessed portion is preferably 0.05 to 0.50 mm.
[0143] <Porous Metal Layer>
[0144] As described above, it is preferred that a porous metal layer be disposed between the electrode stack and the inner bottom surface of the concave container of the battery container so that the porous metal layer and the conductive path of the concave container are connected. That is, when the porous metal layer is disposed, the electrode ( Figure 1 In the case of the all-solid battery shown, the positive electrode 110) and the conductive path ( Figure 1 In the case of the all-solid-state battery shown, the conductive path 181) passes through the porous metal layer ( Figure 1 In the case of the all-solid-state battery shown, the porous metal layer 200 is conductive.
[0145] Since the porous metal layer has pores and is made of metal, it can be easily plastically deformed by applying force in the thickness direction. Therefore, when forming an all-solid battery, the electrode stack is inserted into the outer body by pressing the electrode stack onto the porous metal layer (the metal porous body constituting it), or the electrode stack is pressed onto the porous metal layer (the metal porous body constituting it) by the pressing force of the elastic conductive member, so that the porous metal layer is compressed and deformed, and the electrode on the porous metal layer side of the electrode stack can be well contacted with the sheet-like porous metal substrate, and in addition, the porous metal layer in each all-solid battery when manufacturing multiple all-solid batteries can be homogenized with the degree of conduction of the electrode stack. In the case of using a porous metal layer in an all-solid battery, these effects can further reduce the internal resistance and reduce the deviation of each internal resistance.
[0146] The porous metal layer can be composed of a porous body made of a metal that does not adversely affect the characteristics of the all-solid-state battery, but it is preferred to use a foamed metal porous body [such as "Celmet (registered trademark)" manufactured by Sumitomo Electric Industries, Ltd.] because it is easier to plastically deform it.
[0147] The thickness of the porous metal layer in the all-solid battery is preferably 100 μm or more, and more preferably 150 μm or more, from the viewpoint of ensuring its function more effectively. In addition, there is no particular restriction on the upper limit of the thickness of the porous metal layer in the all-solid battery, but from the viewpoint of suppressing the volume of the components that do not participate in the power generation inside the battery container, it is preferably 1500 μm or less, and more preferably 1000 μm or less.
[0148] The thickness of the porous metal layer is determined from the maximum value of the width in the thickness direction of a cross-section image observed at a magnification of 50 to 1000 times using a SEM (values in Examples described below are determined by these methods).
[0149] It should be noted that, as described above, the porous metal layer is preferably a porous body formed by compressing a metal porous body in the thickness direction, and its thickness is preferably 90% or less of the thickness of the metal porous body (the aforementioned foamed metal porous body, etc.) used to constitute the porous metal layer, and more preferably 80% or less. Therefore, the thickness of the metal porous body (the aforementioned foamed metal porous body, etc.) used to constitute the porous metal layer is preferably 150 to 1000 μm.
[0150] In addition, with regard to the porosity of the metal porous body (the above-mentioned foamed metal porous body, etc.) used to constitute the porous metal layer, from the viewpoint of making the plastic deformation caused by pressing the electrode stack easier and better ensuring the effect of reducing the internal resistance of the all-solid-state battery and suppressing its deviation, it is preferably 99.5% or less, more preferably 99% or less, and further preferably 98.5% or less. From the viewpoint of ensuring sufficient strength for use, it is preferably 80% or more, more preferably 90% or more, and further preferably 95% or more.
[0151] Example
[0152] Hereinafter, the present invention will be described in detail based on examples. However, the following examples do not limit the present invention.
[0153] (Example 1)
[0154] The average particle size of lithium titanate (Li 4 Ti 5 O 12 , negative electrode active material), a sulfide-based solid electrolyte (Li 6 PS 5 Cl) and graphene (conductive aid) were mixed in a mass ratio of 50:41:9 to prepare a negative electrode mixture.
[0155] In addition, LiNbO3 The average particle size of the coating layer is 5 μm. 2 (positive electrode active material), a sulfide-based solid electrolyte (Li 6 PS 5 Cl) and graphene were mixed in a mass ratio of 65:30.7:4.3 to prepare a positive electrode mixture.
[0156] Next, a sulfide-based solid electrolyte (Li 6 PS 5 C1) powder is placed in a powder forming mold, and a pressing machine is used to perform pressure molding at a surface pressure of 70MPa to form a temporary molding layer of a solid electrolyte layer. Further, the above-mentioned negative electrode mixture is configured on the upper surface of the temporary molding layer of the solid electrolyte layer, and pressure molding is performed at a surface pressure of 50MPa to further form a temporary molding layer of the negative electrode on the temporary molding layer of the solid electrolyte layer.
[0157] Next, a foamed metal porous body (thickness: 1.2 mm, porosity: 98%) obtained by cutting a nickel foamed metal porous body [nickel "Celmet" (registered trademark)] made by Sumitomo Electric Industries, Ltd. into a foamed metal porous body with a diameter of 7.25 mm (thickness: 1.2 mm, porosity: 98%) is placed on the temporary molded layer of the negative electrode formed on the temporary molded layer of the solid electrolyte layer, and pressure molding is performed at a surface pressure of 300 MPa to form an integrated product of the solid electrolyte layer and the negative electrode.
[0158] Furthermore, after turning the mold upside down, the positive electrode mixture is arranged on the upper surface of the solid electrolyte layer in the mold (the opposite side of the surface having the negative electrode), and pressure molding is performed at a surface pressure of 50 MPa to form a temporary molded layer of the positive electrode on the solid electrolyte layer.
[0159] Next, a foamed metal porous body obtained by cutting a nickel-made foamed metal porous body identical to the foamed metal porous body used in the negative electrode is placed on the temporary molded layer of the positive electrode formed on the solid electrolyte layer and press-molded at a surface pressure of 1400 MPa to obtain an electrode stack.
[0160] In the obtained electrode stack, the thickness of the negative electrode mixture layer of the negative electrode, the thickness of the porous metal substrate, and the thickness of the porous metal substrate portion embedded in the negative electrode mixture layer were 1400 μm, 60 μm (5% of the thickness of the porous metal substrate before being used for the negative electrode), and 60 μm (100% of the overall thickness of the porous metal substrate). In addition, the area ratio of the portion of the negative electrode mixture exposed on the surface of the negative electrode was 7%.
[0161] In addition, in the obtained electrode stack, the thickness of the positive electrode mixture layer of the positive electrode, the thickness of the porous metal substrate, and the thickness of the portion of the porous metal substrate buried in the positive electrode mixture layer were 800 μm, 60 μm (5% of the thickness of the porous metal substrate before being used for the positive electrode), and 60 μm (100% of the overall thickness of the porous metal substrate). In addition, the area ratio of the portion of the positive electrode mixture exposed on the surface of the positive electrode was 7%.
[0162] In having Figure 1 The inner bottom of a concave container (ceramic depth 2.5 mm) having the same cross-sectional structure as shown, made of ceramic and having a sealing ring made of an iron-nickel-cobalt alloy disposed on the upper part of the side wall, is placed a foamed metal porous body made of nickel that is the same as the foamed metal porous body used in the positive electrode and the negative electrode, cut into a diameter of 7.25 mm, and the above-mentioned electrode stack is placed thereon with the positive electrode at the bottom. Furthermore, on the negative electrode of the electrode stack, a stainless steel plate (thickness 0.3 mm) having the same thickness as the negative electrode is disposed so that the bottom of the concave portion contacts the negative electrode. Figure 1 The cross-sectional shape of the elastic conductive member (the area of the contact surface with the electrode stack in the concave portion is 10 mm 2 ), so that the front end of the stopper is stopped on the lower surface of the supporting portion of the concave container, and the concave portion of the elastic conductive member presses the electrode stack toward the inner bottom surface of the concave container. Then, a sealing body composed of an iron-nickel-cobalt alloy plate (thickness 0.1 mm) is covered on the sealing ring of the concave container, and the sealing body is welded to the concave container (sealing ring), thereby sealing the battery container to obtain an all-solid secondary battery. In the obtained all-solid secondary battery, as described above, the elastic conductive member presses the electrode stack toward the inner bottom surface of the concave container, thereby, the electrode stack presses the porous metal layer composed of the foamed metal porous body. In addition, the thickness of the porous metal layer in the all-solid secondary battery is 200μm.
[0163] (Example 2)
[0164] A fully solid secondary battery was produced in the same manner as in Example 1 except that the amount of the negative electrode mixture and the amount of the positive electrode mixture were changed and an electrode stack having a negative electrode mixture layer thickness of 1120 μm and a positive electrode mixture layer thickness of 640 μm was used. The thickness of the porous metal layer in the fully solid secondary battery was 600 μm.
[0165] (Comparative Example 1)
[0166] A total solid-state battery was produced in the same manner as in Example 1, except that the porous metal substrate composed of the nickel foamed porous metal body was not used in the electrode stack. The thickness of the porous metal layer in the total solid-state secondary battery was 310 μm.
[0167] (Comparative Example 2)
[0168] A solid secondary battery was produced in the same manner as in Example 1 except that the elastic conductive member was changed to a stainless steel plate without a recess (that is, the electrode stack was not pressed against the inner bottom surface of the recessed container). The thickness of the porous metal layer in the solid secondary battery was 400 μm.
[0169] For the all-solid secondary batteries of the embodiments and comparative examples prepared as described above, constant current charging was performed at a current value of 4 mA (3.2 mA for Embodiment 2) until the voltage became 2.6 V, and then constant voltage charging was performed at a voltage of 2.6 V until the current value became 0.05 mA (0.04 mA for Embodiment 2), and then constant current discharge was performed at a current value of 0.4 mA (0.32 mA for Embodiment 2) until the voltage became 1.0 V. Then, for each battery, the internal resistance at 1 kHz was measured with an applied voltage of 10 mV, and the results are shown in Table 1.
[0170] [Table 1]
[0171]
[0172] It can be seen that: compared with the internal resistance values of the all-solid secondary batteries of Examples 1 and 2, the internal resistance values of the all-solid secondary battery of Comparative Example 1 in which the electrode stack does not have a porous metal substrate, and the all-solid secondary battery of Comparative Example 2 in which a metal plate without a recess is used instead of an elastic conductive component and the metal plate does not substantially press the electrode stack toward the inner bottom surface of the concave container are increased, and the current collection is insufficient.
[0173] The present invention can be implemented in other ways than those described above without departing from the scope of the present invention. The embodiments disclosed in this application are examples, and the present invention is not limited to these embodiments. The scope of the present invention is interpreted in accordance with the appended claims in priority to the description of the above specification, and all changes within the scope equivalent to the claims are included in the claims.
[0174] Industrial Applicability
[0175] The all-solid-state battery of the present invention can be used for the same purposes as conventionally known primary batteries and secondary batteries, but because it has a solid electrolyte instead of an organic electrolyte, it has excellent heat resistance and can be preferably used for purposes such as exposure to high temperatures.
[0176] Description of Reference Numerals
[0177] 100, 101 all-solid-state battery; 110 electrode stack; 120 positive electrode; 121 positive electrode mixture layer; 121a positive electrode mixture; 122 sheet-like porous metal substrate; 130 negative electrode; 131 negative electrode mixture layer; 132 sheet-like porous metal substrate; 140 solid electrolyte layer; 150 concave container; 151 bottom portion; 152 side wall portion; 153 opening portion; 154, 155 supporting portion; 160 sealing body; 170 elastic conductive member; 171 locking portion; 172 recessed portion; 180 connecting terminal portion; 181 conductive path; 190 connecting terminal portion; 191 conductive path; 200 porous metal layer; 210 sealing ring; 220 elastic conductive member; 221 supported portion; 222 flat portion; 223 spring portion (spring sheet); 223a boundary; 223b front end portion.
Claims
1. An all-solid-state battery comprising a battery container and an electrode stack accommodated in the battery container, characterized in that: The battery container has a concave container and a sealing body, The concave container includes a bottom portion, a side wall portion, and an opening portion, and has a conductive path extending from the inside to the outside. The opening of the concave container is covered by the sealing body, The electrode stack comprises a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode. The positive electrode comprises a positive electrode mixture layer and a sheet-like porous metal substrate disposed on a surface of the positive electrode mixture layer. At least a portion of the porous metal substrate of the positive electrode, including the end portion on the positive electrode mixture layer side, is buried in the surface layer of the positive electrode mixture layer and integrated with the positive electrode mixture layer, and the other end portion of the porous metal substrate of the positive electrode is exposed on the surface of the positive electrode. The negative electrode includes a negative electrode mixture layer and a sheet-like porous metal substrate disposed on a surface of the negative electrode mixture layer. At least a portion of the porous metal substrate of the negative electrode, including an end portion on the negative electrode mixture layer side, is buried in the surface layer portion of the negative electrode mixture layer and integrated with the negative electrode mixture layer, and the other end portion of the porous metal substrate of the negative electrode is exposed on the surface of the negative electrode. An elastic conductive member is arranged between the electrode stack and the inner bottom surface of the sealing body, The elastic conductive member is electrically connected to the conductive path, and presses the electrode stack toward the inner bottom surface of the concave container.
2. The all-solid-state battery according to claim 1, wherein: The concave container has a support portion that supports the elastic conductive member.
3. The all-solid-state battery according to claim 2, wherein: The elastic conductive member has a locking portion and is fixed to the supporting portion of the concave container via the locking portion.
4. The all-solid-state battery according to claim 1, wherein: The elastic conductive member is a metal plate.
5. The all-solid-state battery according to claim 4, wherein: The elastic conductive member includes a flat surface portion facing the electrode stack and a spring portion rising from the flat surface portion and pressing the electrode stack toward the inner bottom surface of the concave container. The spring portion includes a spring piece that is cantilevered from the planar portion and presses the electrode stack toward an inner bottom surface of the concave container.
6. The all-solid-state battery according to any one of claims 1 to 5, wherein A porous metal layer is provided between the electrode stack and the inner bottom surface of the concave container, and the porous metal layer is electrically connected to the conductive path.
7. The all-solid-state battery according to claim 6, wherein: The porous metal layer is composed of a foamed porous metal body.
Citation Information
Patent Citations
Halide solid electrolyte material and battery using same
WO2020070955A1
Halide solid electrolyte material and battery using same
WO2020070958A1
Battery package, and battery module
WO2022030424A1